2019
DOI: 10.1021/acscatal.8b04481
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Catalyzed Regio- and Enantioselective Markovnikov 1,2-Hydrosilylation of Conjugated Dienes

Abstract: The asymmetric 1,2-Markovnikov hydrosilylation of conjugated dienes with primary silanes catalyzed by a quinolineoxazoline cobalt complex has been described. This protocol provides an efficient approach to chiral allyl dihydrosilanes with high regioselectivity and enantioselectivity (up to 96% ee). The catalyst system is effective for a wide array of conjugated dienes, including mono-and 1,2-disubstituted dienes with aryl and/or alkyl substituents. Further, the products are applied to the synthesis of polyorga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 65 publications
0
45
0
Order By: Relevance
“…Various compounds of transition metals have previously been proved to be effective catalysts for the hydrosilylation of olens and unsaturated polymers. 1,5,30 The most active of them are Pt salts and its complexes. Catalysts based on other Pt-group metals are slightly less active.…”
Section: Effect Of Catalyst Naturementioning
confidence: 99%
“…Various compounds of transition metals have previously been proved to be effective catalysts for the hydrosilylation of olens and unsaturated polymers. 1,5,30 The most active of them are Pt salts and its complexes. Catalysts based on other Pt-group metals are slightly less active.…”
Section: Effect Of Catalyst Naturementioning
confidence: 99%
“…1 2,9-Dimethyl-1,10-phenanthroline (Me2phen) was purchased from Alfa Aesar and was used as received. L1, 2 L2, 3 and L3 4 were synthesized through literature procedures. 4,4'-Ditertbutylbipyridine (dtbpy) was purchased from TCI.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 A common strategy for controlling the selectivity of catalytic reactions that functionalize the C-H bonds of arenes is to incorporate a functional group on the arene that coordinates to a transition-metal catalyst and directs the reaction to C-H bonds that are ortho, meta or para to that functional group. 3 Undirected functionalizations of the C-H bonds of arenes occur with selectivities that are determined by the steric and electronic properties of the various types of C-H bonds. 4 The most classical undirected functionalizations include uncatalyzed or Lewis-acid catalyzed electrophilic aromatic substitution (EAS) processes.…”
mentioning
confidence: 99%
“…The asymmetric 1,2-Markovnikov hydrosilylation of conjugated dienes with primary silanes using pyridine/quinoline-oxazoline chiral Co II dichloride complexes. [60] Angewandte Chemie Minireviews plexes bearing bidentate ligands. [61] In this context, Ge et al reported aCo-catalyzed anti-Markovnikov hydrosilylation of terminal alkynes with both primary and secondary hydrosilanes PhR'SiH 2 (Scheme 12).…”
Section: Minireviewsmentioning
confidence: 99%